2015
DOI: 10.1038/srep11889
|View full text |Cite
|
Sign up to set email alerts
|

High quality thin films of thermoelectric misfit cobalt oxides prepared by a chemical solution method

Abstract: Misfit cobaltates ([Bi/Ba/Sr/Ca/CoO]nRS[CoO2]q) constitute the most promising family of thermoelectric oxides for high temperature energy harvesting. However, their complex structure and chemical composition makes extremely challenging their deposition by high-vacuum physical techniques. Therefore, many of them have not been prepared as thin films until now. Here we report the synthesis of high-quality epitaxial thin films of the most representative members of this family of compounds by a water-based chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…We will not focus our discussions on Ca 3 Co 4 O 9 , as this material has received considerable attention in a recent review article, 35 but we will discuss the growth efforts on Bi 2 Sr 2 Co 2 O y and related compounds. [141][142][143][144][145][146][147][148][149][150] The common techniques used for the growth of cobaltates were pulsed laser deposition, chemical solution deposition, and RF sputtering. Figure 6 documents some of the x-ray (h-2h scans and f-scans) and microscopic analyses performed on thin films of cobaltates.…”
Section: B Cobaltatesmentioning
confidence: 99%
“…We will not focus our discussions on Ca 3 Co 4 O 9 , as this material has received considerable attention in a recent review article, 35 but we will discuss the growth efforts on Bi 2 Sr 2 Co 2 O y and related compounds. [141][142][143][144][145][146][147][148][149][150] The common techniques used for the growth of cobaltates were pulsed laser deposition, chemical solution deposition, and RF sputtering. Figure 6 documents some of the x-ray (h-2h scans and f-scans) and microscopic analyses performed on thin films of cobaltates.…”
Section: B Cobaltatesmentioning
confidence: 99%
“…As a chemical solution route, PAD provides an attractive opportunity to grow films close to thermodynamic equilibrium conditions. The characteristic growth conditions of PAD have already been shown to be advantageous for the stabilization of materials with complex structures or chemical composition, such as misfit cobalt oxides 29 and Y 3 Fe 5 O 12 yttrium iron garnet 30 . On the other hand, PAD might also be useful to clarify the role of structural strain in stimulating spontaneous cationic ordering because it has been shown that structural strain accommodation may proceed in a different way in samples prepared by PAD.…”
Section: Introductionmentioning
confidence: 99%
“…Then the crystal energy is further optimized by reducing crystal symmetry. P-1 crystal group is finally obtained and its optimized lattice parameters are listed in Table 1 together with those of measured ones141529 listed in Table 2. The overall agreement is reasonable and discrepancy mainly results from the extra oxygens in the non-stoichiometric samples.…”
Section: Resultsmentioning
confidence: 99%